(untitled) (Religious dialogue and cooperation, 2024)
Nowadays, social media dominates the practice of communication, sending words, images, and videos at the speed of light (Seitel, 2011). Users of social networks have the opportunity to write, speak, publish, meet other users, and provide a virtual place for meeting, socializing, and interacting. Social media gives users the flexibility to configure their user settings, customize their profiles to look specific, organize their friends or followers, manage what information they want to see or don’t want to see, even give feedback information about what they do, etc. Globalization has made it possible to perceive the world as a whole, to strengthen the sense of belonging, and not to be excluded from the events that take place somewhere on the other side of the world. This paper aims to analyze the relationship between religion and social media, and the subject of research is addressed through the promotion of religion on social media and specifically refers to the situation in the Republic of North Macedonia. The main research question is: How is religion presented on social media? The analysis focuses on the official religious institutions in Macedonia, and through which channels they promote their interests? The primary data source is used using content analysis.